A paisagem de Bonito em Mato Grosso do Sul, sob a ótica dos Sujeitos - Regiane Silvestrini (2021)
The feeling of topophilia leads us to look, reflect and recognize places, evaluating the intimate relationship between man and space through phenomenology. Thus, with a methodology based on semi-directed Bonito interviews, performed with the subjects of Bonito’s landscape, residing for more than 20 years in the municipality of Bonito, Mato Grosso do Sul, this study aimed, through discourse analysis, to understand the interactions between these subjects of Bonito’s landscape with nature, and above all with the elements that compose, modify and degrade the landscapes of the countryside and the city. This research considered the individual’s perception, through their memories and reports of daily life, which unveil aspects of the landscape and guide the understanding of the current organization of its visible elements. The results showed an awareness of changes in landscapes, especially due to the advent of tourism as an economic activity established in the region in the last two decades, in addition to the topophilia relationship of the interviewees considering the social, cultural and environmental importance of the study area and its constituent elements of the landscapes. Furthermore, socio-environmental conflicts related to land use and occupation in the Formoso river basin and sociocultural differences between local residents, the tourist trade and landowners in the municipality of Bonito.